Assessing the challenges faced by informal street traders operating in Durban, South Africa - Luther King Junior Zogli; Nonduduzo Dladla; Bongani Dlamini (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: The informal sector consists of all unregistered businesses operating as street vendors and home-based businesses. Although these businesses employ about 6 out of every 10 workers worldwide, they encounter numerous challenges in carrying out their daily operations. Therefore, in this chapter, the challenges faced by informal traders located in the Durban central district of South Africa’s Kwa-Zulu Natal province are investigated. Design/methodology/approach: This study employs the qualitative research approach utilising structured interviews to obtain data. The Snowball sampling method assisted the researchers to obtain the required data and was analysed using Content Analysis. Findings: The results shows that, lack of business space for trading and storage, lack of funding to expand business, poor hygiene and the lack of ablution facilities for traders as well as municipal harassment were the major constraints of the informal operators.